Does learning more about others impact liking them? Replication and extension Registered Report of Norton et al.’s (2007) lure of ambiguity - Zöe Horsham; Ashleigh Nicola Haydock-Symonds; Hirotaka Imada; Hiu Ching Tai; Wing Lam Lau; Tsz Lui Shum; Yuqing Zeng; Hiu Tung Kristy Chow; Gilad Feldman (Royal Society Open Science)
Norton et al., 2007, demonstrated a counterintuitive phenomenon that knowing other people better and/or having more information about them is associated with decreased liking. They summarized it as ambiguity leads to liking, whereas familiarity can breed contempt. In a Registered Report with a US Prolific undergraduate student sample (N = 801), we directly replicated Studies 1a, 1b and 2 and conceptually replicated Studies 3 and 4 from Norton et al., 2007. Extending their research, we also proposed that curiosity provides an alternative path to liking, hypothesizing that curiosity mediates the relationship between knowledge and liking. Overall, we found weak support for the original findings. Consistent with the original article, participants believed they would like someone who they knew more about (original: h = 0.52–0.70; replication: h = 0.55–0.75) and that knowledge positively predicts liking (original: h = 0.21–0.45; replication: h = 0.57–0.76). However, we found no indication of the number of traits known influencing liking (original: r = −0.43 to −0.005; replication: r = −0.05 to 0.06) or perceived similarity to the target (d = 0.00), for a mediating effect of perceived similarity, for a dissimilarity cascade effect, or for changes in liking or perceived similarity as a factor of learning more about the target. In our extensions, we found support for a positive relationship between curiosity and liking (r = 0.62–0.70), but not for knowledge and curiosity (r = −0.06 to 0.05). Overall, our findings suggest that learning more about others may not influence perceptions of liking, similarity or curiosity towards them. Materials, data and code are available on https://osf.io/j6tqr/. This Registered Report has been officially endorsed by Peer Community in Registered Reports: https://doi.org/10.24072/pci.rr.100947.